Chemical components and emulsification properties of mucilage from Dioscorea opposita Thunb. (1st August 2017) - Ma, Fanyi; Zhang, Yun; Yao, Yanna; Wen, Yurong; Hu, Weiping; Zhang, Jie; Liu, Xiuhua; Bell, Alan E.; Tikkanen-Kaukanen, Carina
Highlights: Mucilage from Dioscorea opposita shows high emulsification. Change in pH does not affect the emulsion stability of mucilage. Mucilage from industrial waste serves as a sustainable resource for natural emulsifier. Abstract: The properties of mucilage obtained from Dioscorea opposita, generated during industrial manufacturing were investigated in this study. Characteristics such as monosaccharide content, amino acid content, molecular weight, and structural features were measured, whereas morphology was observed using a scanning/transmission electron microscope. Additionally, emulsification properties at different concentrations (0.2%, 0.4%, 0.6%, 0.8%, and 1.0%) and under acidic and basic pH (5.0 and 9.0) conditions were studied. The results showed that emulsions prepared from mucilage and medium-chain triglycerides presented more effective emulsifying functions and higher stability, especially at low concentrations. Both, acidic and basic conditions improved the overall emulsification properties, which suggested that the isoelectric point of amino acids may be involved in the emulsification properties. The results of this study show that mucilage from Dioscorea opposita can be considered as a sustainable resource of a natural emulsifier obtained from industrial waste.